Babette's feast [videorecording (DVD)] - Nørgård, Per, 1932- (Criterion collection, 2013)
"At once a rousing paean to artistic creation, a delicate evocation of divine grace, and the ultimate film about food, the Oscar-winning Babette's Feast is a deeply beloved treasure of cinema. Directed by Gabriel Axel and adapted from a story by Isak Dinesen, it is the lovingly layered tale of a French housekeeper with a mysterious past who brings quiet revolution in the form of one exquisite meal to a circle of starkly pious villagers in late nineteenth-century Denmark. Babette's Feast combines earthiness and reverence in an indescribably moving depiction of sensual pleasure that goes to your head like fine champagne."--Back cover of container.